Manajemen Mutu Pembelajaran di SD Kreatif Muhamadiyah Gombong Kebumen - Siti Nurlailiyah (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
This research is based on the importance of the quality of learning. In this regard, this study aims to determine the quality management of learning at Muhammadiyah Gombong Kebumen Creative Elementary School. This study uses qualitative research that focuses on natural empirical phenomena and is analyzed using scientific logic. The data collection techniques in this study were obtained through observation, interviews, documentation and triangulation. Data analysis was carried out by data reduction, data presentation, and data verification then formulating conclusions on the results of the research conducted. The results of this study indicate that the quality management of learning in Muhammadiyah Gombong Creative Elementary School starts from: (1) The teacher plans the lesson by preparing the syllabus, lesson plans, teaching materials, and evaluation tools. (2) Implementation of the standard learning process is carried out by the teacher by implementing content standards and all lesson plans. (3) Evaluation of the learning process includes: evaluation of planning, learning processes, and learning outcomes. (4) Follow-up of the learning process includes: follow-up and improvement of syllabus, lesson plans, teaching materials, and learning evaluation tools, as well as follow-up of learning outcomes.